PENGARUH KECERDASAN EMOSIONAL DAN KOMPETENSI PEDAGOGIK TERHADAP KINERJA GURU DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA SD NEGERI PENAJAM PASER UTARA KALIMANTAN TIMUR - Widjaya, Sukma (Prodi Magister Manajemen Universitas Wijaya Putra, 2024)
This research aims to analyze the influence of emotional intelligence, pedagogical competence, job satisfaction and teacher performance and also to prove and analyze the influence of these variables whether they have a significant effect on Teacher Performance at SD Negeri Penajam Paser Utara, East Kalimantan. This research was conducted at Penajam Paser Utara Elementary School, East Kalimantan. This type of research is quantitative research. Meanwhile, the research method used is explanatory research. The research results show that emotional intelligence influences teacher performance, pedagogical competence influences teacher performance, job satisfaction influences teacher performance. Emotional intelligence influences job satisfaction, pedagogical competence influences job satisfaction. The indirect influence of emotional intelligence on teacher performance through job satisfaction has a positive and significant effect. The influence of pedagogical competence on teacher performance through job satisfaction has a positive and significant effect.